How, when, and for whom: decisions regarding remote neuropsychological assessment during the 2020 COVID-19 pandemic - Bloch, Ayala (Isr J Health Policy Res, 2021)
Neuropsychological assessment provides crucial information about cognitive, behavioral, and socioemotional functioning in medical, educational, legal, and social contexts. During the 2020 COVID-19 pandemic, the Israeli Ministry of Health initially mandated that all psychological assessments be postponed. However, as referrals to time-sensitive, high-need, and high-stakes assessments began to accumulate, it became necessary to consider remote solutions. In the current paper, we describe the considerations that affected the transition to remote activity in a prominent Israeli provider of neuropsychological assessment and rehabilitation services, referring to technological and environmental conditions, cognitive requirements, and tasks, as well as to legal, regulatory, and funding issues. After discussing how assessments should be conducted to maximize feasibility and validity while minimizing risks to clients and clinicians, we propose a preliminary model for deciding whether specific referrals warrant remote administration. The model delineates key factors in decisions regarding remote assessment, emphasizing the distinct roles of the referring clinician and the neuropsychologist who conducts the assessment, and highlighting the need for collaboration between them. The abrupt need for remote assessments during the pandemic required a quick response with little preparation. The lessons learned from this process can be applied in the future, so that the need for remote services can be met with greater certainty and uniformity.